5, 5′-Bis-vanillin derivatives as discriminating sensors for trivalent cations. Issue 26 (24th June 2015) - Costero, Ana M.; Gil, Salvador; Parra, Margarita; Mancini, Pedro M.E.; Kneeteman, María N.; Quindt, Matías I.
Graphical abstract: Abstract: Several bis-vanillin derivatives containing semicarbazone moieties have been prepared and used in discriminating trivalent cations. The prepared probes are readily obtained and they are usually highly crystalline. Depending on the ligand and the studied cations, quenching, enhancement or no changes in the fluorescence spectrum were observed. Using a series of the prepared ligands allows distinguishing between Fe 3+, Cr 3+ and Al 3+ . Detection limits and selectivity in front of divalent cations have been evaluated.